1999
DOI: 10.1111/j.1600-0684.1999.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

The disruption of macaque CD4 + T‐cell repertoires during the early simian immunodeficiency virus infection

Abstract: T-cell receptor (TCR) complementarily determining region 3 (CDR3) spetratyping analysis was employed to assess the ability of an AIDS virus to disrupt CD4 + T-cell repertoires during the primary infection. Rhesus and pig-tailed macaques infected with simian immunodeficiency virus (SIV)mac 251 and SIVsmmFGb, respectively, were evaluated. Following SIV infection, the macaques exhibited an apparent decline of CD4 + peripheral blood lymphocyte (PBL) counts, which was associated with a change in CDR3 profiles from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
4
5
0
Order By: Relevance
“…This conclusion is similar to that reached by Zhou et al studying BCG/SIVmac co-infections in rhesus monkeys [24,25]. These investigators observed a transient decrease in viral loads after BCG co-infection in early SIVmac-infected animals that was associated with the development of BCG-driven proliferation of PBL with a TCR CDR3-dependent expansion of Vb-expressing memory CD4+ and CD8+ cell subpopulations [24,25]. In the studies by Zhou et al, the SIVmac/BCG co-infected rhesus monkeys were ini- tially protected from AIDS progression, but eventually experienced a rapid decline in circulating CD4 + T-cells and rapid AIDS progression.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This conclusion is similar to that reached by Zhou et al studying BCG/SIVmac co-infections in rhesus monkeys [24,25]. These investigators observed a transient decrease in viral loads after BCG co-infection in early SIVmac-infected animals that was associated with the development of BCG-driven proliferation of PBL with a TCR CDR3-dependent expansion of Vb-expressing memory CD4+ and CD8+ cell subpopulations [24,25]. In the studies by Zhou et al, the SIVmac/BCG co-infected rhesus monkeys were ini- tially protected from AIDS progression, but eventually experienced a rapid decline in circulating CD4 + T-cells and rapid AIDS progression.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, there is a correlation between the preservation of these subsets and protection from AIDS progression and death. This conclusion is similar to that reached by Zhou et al studying BCG/SIVmac co-infections in rhesus monkeys [24,25]. These investigators observed a transient decrease in viral loads after BCG co-infection in early SIVmac-infected animals that was associated with the development of BCG-driven proliferation of PBL with a TCR CDR3-dependent expansion of Vb-expressing memory CD4+ and CD8+ cell subpopulations [24,25].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations